Multigenerational Transmission of Culture - Daniel Spiro (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper explores intergenerational transmission of culture and the consequences of a plausible assumption: that people care not only for their children's culture but also for how their grand-children are raised. This departs from the previous literature which, without exception, assumes parents either do not care about, or fail to consider, the effect their actions have on all future generations. The current paper models a sequential game where parents take actions trading off being close to their own preferences and influencing their children, and where parents take into account that the children face a similar trade-off when raising their children. Predictions regarding endogenous extremism, the effect of societal socialization, parents. discounting, social pressure and interaction between groups are derived. In equilibrium, parents behave more extremely than their own preferences and this effect is intensified the more extreme preferences the parent has. There may be perpetual extremizing whereby an arbitrarily long sequence of generations will behave more extremely than the first ancestor's preferences. Furthermore, interaction of groups implies more extreme initial behavior but also faster integration.
Keywords: D90; J15; Z10; 330; culture; integration; social pressure